Strengthening Values and Norms for Information Technology Navigation in Grade IV Elementary School Students - Fajri, Sabila Auliya; Sukartono, S (Universitas Muhammadiyah Surakarta, 2023)
Purpose: (1) Describes the reinforcement of values and norms as students navigate technology and information, (2) Explores the supporting and inhibiting factors for strengthening values and norms as students navigate technology and information, (3) Proposes a suitable solution to overcome the factors inhibiting the strengthening of values and norms as students navigate technology and information. Methodology: This qualitative research employs a survey design methodology. Data collection encompasses in-depth interviews, observation, and documentation. The study involves school principals, teachers, and students as its subjects. To ensure data validity, triangulation methods such as data triangulation, incorporating source and technical triangulation, are employed. Results: The findings indicate that values and norms significantly shape students’ responses to advancements in information technology. Extracurricular activities and structured projects are pivotal in imparting valuable lessons to students. However, it is essential to recognise that all supportive elements can potentially hinder progress if not utilised to their fullest extent. Establishing a supervisory team to oversee the implementation of these practices emerges as a crucial initial measure to ensure program consistency. Moreover, initiatives involving educators, parents, and the wider community can foster emotional bonds and a shared sense of responsibility among stakeholders. Applications/Originality/Value: This study is significant in integrating the reinforcement of values and norms within students’ engagement with information technology, both within the structured curriculum and through extracurricular activities.